Shopping cart design for native-based shopping mall system - Yeo, Chong Hui. (2008)
With the advent of Internet and friendly GUI-based Web browser, many e-shopping sites sprung up to catch hold of the wave that have been sweeping across the world; to sell their products by electronic means via the World Wide Web. These e-shopping sites provide different services but they have one thing in common; the Web sites are 2-D in nature and they does not allow users to interact with each other.